Comparison of Vaginal and Sublingual Misoprostol for Second Trimester Abortion : Randomized Controlled Equivalence Trial - von Hertzen, H. (2012)
BACKGROUND: To identify an effective misoprostol-only regimen for the termination of second trimester pregnancy, we compared sublingual and vaginal administration of multiple doses of misoprostol in a randomized, placebo-controlled equivalence trial. METHODS: Six hundred and eighty-one healthy pregnant women requesting medical abortion at 13-20 weeks' gestation were randomly assigned within 11 gynaecological centres in seven countries into two treatment groups: 400 microg of misoprostol administered either sublingually or vaginally every 3 h up to five doses, followed by sublingual administration of 400 microg misoprostol every 3 h up to five doses if abortion had not occurred at 24 h after the start of treatment. We chose 10% as the margin of equivalence. The primary end-point was the efficacy of the treatments to terminate pregnancy in 24 h. Successful abortion within 48 h was also considered as an outcome along with the induction-to-abortion-interval, side effects and women's perceptions on these treatments. RESULTS: At 24 h, the success (complete or incomplete abortion) rate was 85.9% in the vaginal administration group and 79.8% in the sublingual group (difference: 6.1%, 95% CI: 0.5 to 11.8). Thus, equivalence could not be concluded overall; the difference, however, was driven by the nulliparous women, among whom vaginal administration was clearly superior to sublingual administration (87.3% versus 68.5%), whereas no significant difference was observed between vaginal and sublingual treatments among parous women (84.7% versus 88.5%). The rates of side effects were similar in both groups except for fever, which was more common in the vaginal group. About 70% of women in both groups preferred sublingual administration. CONCLUSIONS: Equivalence between vaginal and sublingual administration could not be demonstrated overall. Vaginal administration showed a higher effectiveness than sublingual administration in terminating second trimester pregnancies, but this result was mainly driven by nulliparous women. Fever was more prevalent with vaginal administration. Registered with International Standard Randomized Controlled Trial number ISRCTN72965671.